Cholinergic Pathway Suppresses Pulmonary Innate Immunity Facilitating Pneumonia After Stroke. Issue 11 (November 2015) - Engel, Odilo; Akyüz, Levent; da Costa Goncalves, Andrey C.; Winek, Katarzyna; Dames, Claudia; Thielke, Mareike; Herold, Susanne; Böttcher, Chotima; Priller, Josef; Volk, Hans Dieter; Dirnagl, Ulrich; Meisel, Christian; et al.
Abstract : Background and Purpose—: Temporary immunosuppression has been identified as a major risk factor for the development of pneumonia after acute central nervous system injury. Although overactivation of the sympathetic nervous system was previously shown to mediate suppression of systemic cellular immune responses after stroke, the role of the parasympathetic cholinergic anti-inflammatory pathway in the antibacterial defense in lung remains largely elusive. Methods—: The middle cerebral artery occlusion model in mice was used to examine the influence of the parasympathetic nervous system on poststroke immunosuppression. We used heart rate variability measurement by telemetry, vagotomy, α7 nicotinic acetylcholine receptor–deficient mice, and parasympathomimetics (nicotine, PNU282987) to measure and modulate parasympathetic activity. Results—: Here, we demonstrate a rapidly increased parasympathetic activity in mice after experimental stroke. Inhibition of cholinergic signaling by either vagotomy or by using α7 nicotinic acetylcholine receptor–deficient mice reversed pulmonary immune hyporesponsiveness and prevented pneumonia after stroke. In vivo and ex vivo studies on the role of α7 nicotinic acetylcholine receptor on different lung cells using bone marrow chimeric mice and isolated primary cells indicated that not only macrophages but also alveolar epithelial cells are a major cellular target of cholinergic anti-inflammatory signaling in the lung. Conclusions—: Thus, cholinergic pathways play a pivotal role in the development of pulmonary infections after acute central nervous system injury. Abstract : Supplemental Digital Content is available in the text.